Sex ratio and virulence in two species of lizard malaria parasites - Pickering, J; Read, A; Guerrero, S; West, SA (2000)
Evolutionary theory predicts that both the virulence and the sex ratio of a parasite can depend upon its population structure, and be positively correlated. With only one or a low number of strains within a host, a low sex ratio and a relatively low virulence are predicted. With high numbers of strains within a host, a more even sex ratio and a high parasite virulence are predicted. We examined gametocyte sex ratio and a possible correlate of virulence, parasite density (parasitaemia), in natural populations of two species causing lizard malaria, Plasmodium 'tropiduri' and P. balli. The mean sex ratios of both species were female-biased, consistent with estimate selfing rates of 0.36 and 0.48 respectively. In P. 'tropiduri', as we predicted, a positive correlation was also observed between our measure of virulence, parasitaemia and the gametocyte sex ratio. Furthermore, the gametocyte sex ratio was positively correlated with gametocyte density (gametocytaemia). This is consistent with facultative sex allocation in response to variable population structure if gametocytaemia is an indicator of the number of clones within a host. These relationships were not observed in P. balli.